Buy Now or Buy Later: Mediating Role of Buying Interest in Purchasing Decisions - Marsudi; Fika Fitriasari (Universitas muhammadiyah malang, 2023)
This study aims to reveal and analyze the importance of the role of buying interest in the relationship between giving discounts and consumer purchasing decisions on a product at the Ramayana department store in Malang. Although it has given many discounts and is often done, but if it cannot generate consumer buying interest in the product, then the consumer does not decide to buy the product offered. This study uses a quantitative descriptive method with variables consisting of price discounts, buying interest, and purchasing decisions. The population of this study are consumers who have purchased products at the Ramayana department store in the city of Malang. The number of samples used in this study were 100 respondents using purposive sampling technique and collecting data using a questionnaire. Meanwhile, the data analysis used was path analysis to test the direct and indirect effects. The results of the study show that price discounts have a significant effect on purchasing decisions, price discounts have a significant effect on purchase intention, purchase intention has a significant effect on purchasing decisions, and price discounts have a significant effect on purchasing decisions through purchase intention.